Pengembangan Elektroda Komposit Polianilin-Epoksi Grafena Oksida-Kobalt Oksida melalui Optimasi Komposisi dan Ketebalan sebagai Sensor Fosfat - Intan Puspita Dewi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
The rapid development of materials science allows composites to be used as ion detection electrodes. The composite electrode developed in this research is based on polyaniline (PANI), epoxy, graphene oxide (GO) and cobalt oxide (CoO) as a sensor to detect phosphate ions using potentiometric method. PANI and epoxy were used as matrix because they have good electrical and mechanical properties, good environmental stability and easy to synthesize. Modification of GO and CoO were chosen because GO can increase the sensitivity of PANI and CoO can give unique properties to the composite that is able to interact with phosphate. The development of composite electrodes includes optimization of composition and thickness. Optimization was done by measuring the standard solution to determine the optimal response of the composite electrode in detecting phosphate ions. Electrode performance was reviewed through the value of sensitivity, linearity, precision (repeatability and reproducibility) and detection limits. The optimum electrode composition was found in the ratio of PANI: Epoxy: GO:CoO 0,4: 0,2: 0,3: 0,3 with a sensitivity of -17,105 mV / decade (R2 = 0,982) and the optimum thickness of the electrode was found at a thickness of 2 mm with a sensitivity of 28,981 mV/decade (R2 = 0,988). Repeatability values ranged from 0.10 % -1.56 %, the value of 0.61% reproducibility and limit detection value of 6.87 x 10-7 M. This result showed that PANI-Epoxy-GO-CoO electrode has a high level of precision because it has a good level of accuracy and consistency because % RSD < 5 %. The feasibility of the electrode was tested by measuring phosphate ions in a soil sample. Feasibility tests showed that the concentration of phosphate ions detected was 6.81 x 10-4 M. The results of this study showed that the composite electrode PANI-Epoxy-GO-CoO has the ability to detect phosphate ions in soil samples.
Reupload File Repository 19 Mei 2026_Yudi Approved by Teddy
Keywords: Composite electrode; composition; phosphate; potentiometry; and thickness